Rock blasting practices in Malaysian quarry industries / Muhammad Farhan Zulkifli - Zulkifli, Muhammad Farhan (Faculty of Architecture, Planning and Surveying, 2009)
Rock blasting is the controlled use of explosives to excavate or remove rock. It is a technique used most often in mining and civil engineering such as dam construction, road work and quarry. Blasting brought a new dimension to engineering excavation work in Malaysia. It is common now to cut wider and better aligned highways through hills instead of having to avoid around it as in the older roads. Blasting is also used in development sites to reduce land to the required levels, for excavation or basements and for landscaping of in situ rocks in construction of theme parks. Usually constructions are near build-up and populated areas; the blasting engineer has to blast cautiously to reduce environmental problems. While explosives are useful tools for quarries and engineering excavations, they are also dangerous tools. Safety measures have to be emphasized and practiced at all stages in their storage, transportation, usage, disposal and management.